Implementasi Pendidikan Karakter melalui Mata Pelajaran Pendidikan Agama Islam pada Masa Pandemi Covid-19 - Lubis, Rahmat Rifai; Nasution, Indah Widya Jaya Putri; Audilla, Vira; Hasanah, Rizki; Abidin, Wimbi Achmad Sauqi Zainal (STAI Auliaurrasyidin Tembilahan, 2022)
This study aimed at finding out the implementation of character education through Islamic Religious Education during the Covid-19 period at Darul Ilmi Murni Private Junior High School. The study focused on three domains, namely planning, implementing, and evaluating the character education in Islamic Religious Education learning during the Covid-19 period. This research was qualitative. The subjects were principals and PAI teachers. The data were collected using observation, documentation, and in-depth interviews. The results indicated that in the planning process for character education during the COVID-19 pandemic, an educator is required to prepare an attractive lesson plan. While in the implementation of character education, educators instill character values with the method of inquiry, discussion, question and answer, lectures, giving advice, and the Al-Quran Tahfidz program. Meanwhile, the evaluation aspect is carried out through communication and assessment sheets